((Drafting diacritics in the art of abstract expressionism and its reflection on the artistic productions of art education students)) (Journal of the College of Basic Education, 2022)
The research marked ((Formulation of composition in the art of abstract expressionism and its reflection in the artistic productions of art education students)). Its importance is in shedding light on this topic as ideas were established in the concepts of drafting formation in the art of artistic accomplishments and the visual vision of the contemporary plastic scene. The research aims to identify the composition formulation and the mechanism for the operation of raw materials in this art, and to indicate the extent of its reflection in the artistic productions of art education students. The emergence of abstract expressionism, its methods, features, characteristics and most important techniques were reviewed with examples of the productions of its most prominent artists. A field study was conducted to examine the students' outputs, which amounted to (75) products for students of the Department of Art Education at the College of Fine Arts - University of Baghdad, and (12) artistic productions were selected as a sample It was analyzed according to a special form prepared specifically for this purpose, and a number of results and conclusions were reached, the most important of which was the reflection of freedom in intellectual and conceptual propositions with a high percentage in the students' outputs, as it was clearly shown that there is a direct effect of abstract expressionism on the results and in more than one field. They are influenced by the use of abstraction of shapes to express self-states and emotions, as well as their use of techniques such as gluing, collage, mixing, and the use of various colors and different materials as well as their reliance on chromatic contrast to obtain emotional shock, not to mention showing the difference in the texture of the painting.